Phenomenon of Videogame Culture in Modern Society - Horban, Olexander; Martych, Ruslana; Maletska, Maria (Studia Warmińskie, 2019)
In given article the philosophical reflection of the game as a special type of social reality with its specific subject-object and subject-subject relations is conducted. In the epoch of digital reality, videogames become the dominant type of games, which has been phenomenalized into a special type of culture. The phenomenon of videogame culture lies in the fact that videogames form a special space and community, specific rules and ethics, create their own unique material and virtual artifacts. Videogame culture has a significant impact on the socialization, worldview and value orientations of the individual.